Astma pokarmowa – za - Buczyłko, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Some foods are capable of provoking asthmatic symptoms. In over 8% of children, the aetiology of asthma was food-related. Children admitted to intensive care were significantly more likely to report food allergy (FA) – 7 times more at least one FA compared with children seen in the ambulatory setting. The association was stronger among children with multiple or severe FA. Children with FA developed asthma earlier and at higher prevalence. Asthma mortality in children and young adults: FA and inadequate treatment were the major risk factors. An alarming finding was that 11 of the 37 deaths were probably caused by FA. Asthma and FA co-exist in approximately one-third of children. When both conditions are present a patient is placed at greater risk of having a fatal reaction. For this reason asthma should be diligently managed in an FA patient and these patients should be carefully instructed on allergen avoidance and the use of epinephrine. Of the 13 children and adolescents with fatal or near-fatal anaphylactic reactions to foods, 12 had asthma that was well controlled. All had known FA, but had unknowingly ingested the foods responsible for the reactions. The reactions were to peanuts, nuts, eggs, and milk, all of which were contained in foods such as candy and pastry. Determination of plasma IL-4 and IL-5 levels can be a useful tool for evaluation of the effects of food challenge tests on children with asthma and coexisting IgE-dependent FA. Patients with allergies to > 1 food had increased asthma hospitalizations and use of oral steroids. Food allergy may be a risk factor for increased asthma morbidity in adults. An association between plane tree pollen allergy and plant food allergy has been described. Non-specific lipid-transfer proteins in plane pollen were characterized as a minor allergen in plane pollen-allergic patients without food allergy and as a major allergen in plane pollen-allergic patients with peach allergy. It is an example of a new concept with wide practical applications for clinicians.